Functional analysis of a novel FBN1 deep intronic variant causing Marfan syndrome in a Chinese patient - Wang, Qingming; Zhang, Fang; Zhou, Xinlong; Li, Hui; Zhao, Juan; Yuan, Haiming (Frontiers in Genetics, 2025)
Marfan syndrome (MFS MIM#154700), due to pathogenic variants in the FBN1 gene, is an autosomal dominant connective tissue disorder, typically involving the skeletal, cardiovascular and ocular systems. Currently, over 3000 MFS patients were reported, and approximately 1800 pathogenic variants in FBN1 were identified. However, the molecular diagnosis still remains challenging for 8%–10% of patients with clinical features suggestive of MFS. In this study, we reported a 2-month-old Chinese female patient whose clinical features were compatible with the MFS. Whole-exome sequencing (WES) identified a novel de novo deep intronic variant, c.4943-8_4943-7insTATGTGATATTCAT TCAC in intron 40 of FBN1 that was predicted to affect the RNA splicing. Minigene analysis showed that this variant causes skipping of exon 41, leading to the deletion of 41 amino acids (c.4943_5065del, p.Val1649_Asp1689del). It confirmed the pathogenic nature of the variant and established the genotype-phenotype relationship. Our study expands the mutation spectrum of FBN1 and emphasizes the importance of deep intronic variant interpretation and the need for additional functional studies to verify the pathogenicity of these variants.